Multi-channel extraction methods for event-related potentials - Lee, Wee Lih (Curtin University, 2014)
Event-related potentials (ERPs) are neural activities that are generated in response to an event. In recent decades, multi-channel EEG recordings have been increasingly adopted in ERP studies. In this thesis, to extract an ERP-of-interest, single-trial multi-channel extraction methods have been developed. The developed methods are data-driven and thus avoid human intervention during ERP analyses. For this reason, they are also practical for real-time applications such as brain-computer interface (BCI).